Ascorbate absorption by live channel catfish as a function of ascorbate concentration, pH, and-duration of exposure - Thed, S.T.; Erickson, M. C.; Shewfelt, R. L. (Wiley-Blackwell, 1993)
Ascorbate uptake by muscle tissue of live channel catfish was affected by ascorbate concentrations (1000, 2000, and 3000 ppm), pH (5, 6, and 7) and duration of exposure (8, 16, and 24 hr.). The most favorable conditions for ascorbate absorption were exposure to 3000 ppm ascorbate at pH 5 for 24 hr. The increased muscle ascorbic acid concentration was 4-fold higher than that of the control group (10 ppm). The ability of live channel catfish to absorb dissolved ascorbate via gills and/or intestines and distribute the antioxidant into muscle tissue provides a new approach to introduce water-soluble antioxidants to aquacultured fish species.